Structural Study Of Twaka Shareera W.S.R To Visarpa - Channaveeragouda , B H; Patil, Mahesh R; Giritammanavar, J T; Butali, Kavita; Mohan, G Vinay (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda describe the organization of the body in term of doshas, dhatus and malas. Twacha is one among the updhatus which provide protective layer over the body that protect from the heat, cold & external infection. The union of Shukra (spermatozoa) & Shonita (ovum) while being cooked (processed by heat) give rise to the formation of seven twaka (skin) just like formation of cream when milk is boiled. Acharya Susruta and other Acharyas are described twaka shareeram in detail. Acharya Susruta defined Twacha as Upadhatu of mamsa dhatu.Twacha is one among the Panch jyanendriya, which carry sensation of touch.& It covers external part as well as internal part of body. Since antiquity human being often suffered from many type of diseases, out of them skin disease is one of the major problem for the community, because there is a change in the structural appearance of the skin & it make entire body ugly. There are different theories among the Acharyas regarding the number of layers. Acharyas Charaka consider that Twacha is made up of six layers where others. Acharya Susruta considers seven layers. In this layers of twacha, different type of diseases observe in different layers. Out of this, a very commonly seen “Visarpa” disease is found in one of the Twacha layer.“Visarpa” is one among the type of skin disorder which is common and acute disorder of Twacha. Acharyas describe symptoms of Visarpa like – spreading character, Inflammation, Pricking type of pain, Fever, Vesicles, Segmental spreading, Redness, Rapid spreading. Although Twacha has been explained in our classic, we get very vague and very less description about the disease related to Twacha shareera. And it is outermost protective layer of the body, so it becomes essential to know the structural and anatomical changes occur in the Visarpa. Now a day’s Visarpa disease largely spread in the human being. While diagnosing the patients of Visarpa, there is difficulty regarding the identification of structural deformity, hence need is felt to study the Visarpa & twak shareera.